Ameliorative effects of N‐acetyl cysteine on diclofenac‐induced renal injury in male rats based on serum biochemical parameters, oxidative biomarkers, and histopathological study. Issue 8 (18th June 2019) - Nouri, Ali; Heidarian, Esfandiar
Abstract: Diclofenac (DIC) can cause nephrotoxicity in humans. In this study, we evaluated the protective effects of N ‐acetyl cysteine (NAC) on DIC‐induced nephrotoxicity. Rats were assigned to four groups. Group 1 was control group; group 2 administrated with DIC only; group 3 administrated with DIC plus NAC and group 4 was treated with DIC and silymarin. Then, the oxidative biomarkers in serum and kidney were evaluated. In group 2, DIC caused a remarkable elevation ( p  < 0.05) in the levels of serum uric acid, TNF‐α, creatinine, urea, GOT, and GPT, protein carbonyl, malondialdehyde (MDA), and renal TNF‐α gene expression, relative to control group. In treated groups with NAC and silymarin, a noticeable reduction ( p  < 0.05) was seen in mentioned levels of biochemical parameters. NAC showed that it could reduce the abnormality of biochemical parameters and histopathological changes which is induced by DIC. Practical applications: N ‐acetyl cysteine (NAC) has a potential to ameliorate renal histopathological changes and improving renal activity of antioxidant enzymes in nephrotoxicity by diclofenac. Also, NAC has a potential to reduce inflammatory gene expression in the diclofenac‐induced nephrotoxicity. Additionally, NAC can be considered as an antioxidant which reduces renal MDA and serum protein carbonyl due to nephrotoxicity by diclofenac. Abstract : N ‐acetyl cysteine has a potential to ameliorate renal histopathological changes and improving renal activity of antioxidant enzymes in nephrotoxicity by diclofenac. N ‐acetyl cysteine has a potential to reduce inflammatory gene expression in the diclofenac‐induced nephrotoxicity. N ‐acetyl cysteine can be considered as an antioxidant which reduces renal malondialdehyde and serum protein carbonyl due to nephrotoxicity by diclofenac.